Neighbourhood poverty, work commitment and unemployment in early adulthood: A longitudinal study into the moderating effect of personality - Nieuwenhuis, Jaap; Yu, Rongqin; Branje, Susan; Meeus, Wim; Hooimeijer, Pieter (Public Library of Science, 2016)
We studied how personality moderates the effect of neighbourhood disadvantage on work commitment and unemployment in early adulthood. Using a personality typology of resilients, overcontrollers, and undercontrollers, we hypothesised that the association between neighbourhood poverty and both work commitment and unemployment would be stronger for overcontrollers and undercontrollers than for resilients. We used longitudinal data (N = 249) to test whether the length of exposure to neighbourhood poverty between age 16 and 21 predicts work commitment and unemployment at age 25. In line with our hypothesis, the findings showed that longer exposure was related to weaker work commitment among undercontrollers and overcontrollers and to higher unemployment among undercontrollers. Resilients' work commitment and unemployment were not predicted by neighbourhood poverty.
Keywords: General Medicine; General Biochemistry,Genetics and Molecular Biology; General Agricultural and Biological Sciences; SDG 8 - Decent Work and Economic Growth